2014
DOI: 10.1111/vcp.12183
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative morphologic, cytochemical, and ultrastructural characteristics of blood cells in captive Asian water monitors

Abstract: Background: The Asian water monitor (Varanus salvator) is the most common monitor lizard in Thailand. Reported data regarding hematology and morphology of blood cells for this species are scarce. Objectives: The objective of this study was to assess routine hematologic variables and characterize the morphology, cytochemical staining, and ultrastructural features of blood cells in the Asian water monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
37
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 9 publications
25
37
0
4
Order By: Relevance
“…The MCV of the BSK was smaller than that of the BrK, BK, painted stork, lesser adjutant, greater adjutant, great argus, and crested serpent eagle ( Spilornis cheela ) . The morphometric analysis of RBCs in the three kite species of this study showed a correlation with the MCV.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The MCV of the BSK was smaller than that of the BrK, BK, painted stork, lesser adjutant, greater adjutant, great argus, and crested serpent eagle ( Spilornis cheela ) . The morphometric analysis of RBCs in the three kite species of this study showed a correlation with the MCV.…”
Section: Discussionmentioning
confidence: 47%
“…Differential leukocyte (white blood cell, WBC) counts were assessed by counting 200 cells, and the final data represent the averaged counts between two clinicians. The total erythrocyte (red blood cell, RBC) and WBC counts were determined manually with the improved Neubauer counting chamber after 5 µL of blood were diluted by mixing with 1 mL of a Natt and Herrick solution to obtain a 1:200 solution as described previously . As thrombocytes in the Natt and Herrick solution were difficult to differentiate from lymphocytes, the number of thrombocytes per microliter of blood was not determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that hemogregarine infection was associated with an enhanced erythropoiesis, most likely due to low‐grade hemolysis. Hemogregarine parasite infection is usually reported as nonpathogenic in reptiles, and unassociated with decreased PCV or RBC counts . The hemogregarine Hemolivia mariae has been reported to infect Bobtail lizards in South Australia .…”
Section: Discussionmentioning
confidence: 99%
“…Hemogregarine parasite infection is usually reported as nonpathogenic in reptiles, and unassociated with decreased PCV or RBC counts. 17,18 The hemogregarine Hemolivia mariae has been reported to infect Bobtail lizards in South Australia. 13 Further studies to identify the causative hemogregarine species and assess its pathogenicity in Western Australian Bobtail lizards are warranted.…”
Section: Discussionmentioning
confidence: 99%